Nursing Students’ Perception of Their Learning Style - Kristina Lisum; Sondang Ratnauli Sianturi (Jurnal Keperawatan, 2020)
Identification and socialization about importance of nursing students’ learning style should be performed by nursing educator to achieve learning goals.  The purpose of this study is to explore nursing students’ perception of their learning style. Method of this study was qualitative with descritive interpretative design involving 10 nursing students, using purposive sampling. Students were divided into two groups, there were academic and profesion group continued by focus group discussion (FGD). The analysis data used  thematik analysis content with Collaizi method.  The results of this study  consists of five themes, namely : (1) easy and comfort ways to learn (2) variation of learning strategy at classroom and clinic   (3)  think, analyse about theory and use it at practice  (4) influence of passing the nurse national competency test   (5)  more profesional and contribute to nurses development. It was recommended to nurses educator at nursing school to identify sthrengthness of nursing student toward milenial learning style.  In order to improve learning outcome, nurse educator must combine variation  teaching strategy with nursing students’ learning style Keywords : learning, learning styles, nursing students, perception of nursing students.